Transcriptional activation of endogenous retroviral sequences in human epidermal keratinocytes by UVB irradiation - Hohenadl, Christine; Germaier, Herbert; Walchner, Monika; Hagenhofer, Manuela; Herrmann, Martin; Stürzl, Michael; Kind, Peter; Hehlmann, Rüdiger; Erfle, Volker; Leib-Mösch, Christine (The journal of investigative dermatology, 1999)
Ultraviolet radiation is a pathogenic factor in various diseases, e.g., autoimmune disorders such as lupus erythematosus. On the other hand, endogenous retroviruses are discussed as etiologic agents in lupus erythematosus. Therefore, we investigated the influence of ultraviolet irradiation on expression of human endogenous retroviral sequences and human endogenous retroviral sequence promoter-driven transcription of cellular genes using human epidermal keratinocytes as a model system. First, conserved sequences of endogenous retroviral pol genes were amplified from cellular mRNA by reverse transcriptase polymerase chain reaction with degenerate oligonucleotide primers. Polymerase chain reaction products were hybridized in a reverse dot blot hybridization assay to a representative number of distinct cloned human endogenous retroviral pol fragments. Using this method, we could show that irradiation with 30 mJ per cm2 ultraviolet B activates transcription of various endogenous retroviral pol sequences in primary epidermal keratinocytes as well as in a spontaneously immortalized keratinocyte cell line (HaCaT). Interestingly, some of these sequences were found to be closely related to pol sequences of human endogenous retroviral sequences which have been shown to be expressed in autoimmune patients. Analysis of human endogenous retroviral pol expression in vivo using skin biopsies of lupus erythematosus patients revealed similar activation patterns. In a second approach, ultraviolet B- induced chimeric transcripts were isolated which are initiated by human endogenous retroviral promoters and proceed into cellular sequences using a newly established modified differential display polymerase chain reaction technique. The activation of human endogenous retroviral sequence transcription by ultraviolet B may contribute to the pathogenesis of lupus erythematosus, where inappropriate antigenic presentation of ultraviolet B-induced viral and cellular proteins could stimulate autoantibody production.
Elektronische Reproduktion der Druckausgabe
Gesehen am 23.05.2022